Strategic disruption of management competencies in micro and small enterprises: A literature review - Castro Ijiri, Gabriela Lizeth (2024)
This article reports on the evolution of scientific production in indexed journals regarding managerial skills from a strategic perspective of micro and small enterprises (MSEs). The methodology employed was a bibliometric analysis with document analysis techniques of articles published in the Scopus, Web of Science, and Taylor & Francis databases. Search filters with the keywords “Management competencies” and the target population (micro and small enterprises) were applied for the selection of research. For this purpose, bibliometric measures were evaluated that assess authors' productivity based on the number of documents consulted and included, as well as by years, countries, and keywords. Furthermore, multiple multidimensional indicators of collaboration among authors were examined, and this information was supplemented with the analysis of bibliographic platforms. In this regard, it's crucial for managers of micro and small enterprises to combine their management skills, creativity, and entrepreneurial spirit to make accurate short and long-term decisions, thereby ensuring the future success of the company. These obtained results can be used for new inquiries and studies, while also posing a challenge for the evolution of managerial competencies in the coming years.